Web-Based Employee Attendance Information System On CV. Syntax Corporation Indonesia - Amelia Amelia; Mar'atus Solikhah (Jurnal Indonesia Sosial Teknologi, 2023)
This study discusses the implementation of a Web-Based Employee Attendance Information System on a CV. Syntax Corporation Indonesia. The application of information technology in employee attendance management has become an increasingly urgent need in various organizations, including CV companies. Syntax Corporation Indonesia faces the challenge of efficient and accurate attendance management. The Information System developed in this study is designed to facilitate recording and monitoring employee attendance and allow real-time data access through an intuitive web interface. This research includes needs analysis, system design, software development, and practical implementation of the Employee Attendance Information System. The development method used is a software development life cycle model that includes requirements analysis, design, development, testing, and implementation. The results of this study show that the Web-Based Employee Attendance Information System implemented in CV. Syntax Corporation Indonesia has improved the efficiency and accuracy of attendance management. Employees can easily record their attendance through the web interface, while management can access real-time attendance data and generate relevant reports. In addition, implementing this Information System also allows for more effective attendance monitoring, detection of unauthorized attendance, and taking appropriate actions per company regulations.